Dietary supplement-wheat germ’s effect on the spectrum of lipoproteins and fatty acids in the blood of experimental hyperlipidemic animals - Azizova, Dilzoda M. (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The present study was designed to investigate the effect of dietary supplement- wheat seedling on the serum of blood lipids and the fatty acid composition in animals with experimental hyperlipidemia model. Material and methods: Thirty male rabbits – Chinchilla breed were divided into 5 groups: intact rabbits, animals with experimental model of hypercholesterolemia, adjustment of experimental hypercholesterolemia statin, adjustment of experimental hypercholesterolemia of wheat seedling, adjustment of experimental hypercholesterolemia statin and wheat seedling. The experimental hypercholesterolemia was reproduced by intragastric daily administration of cholesterol of 0.2 g per kg of mass for 2 months. During treatment ultrox and wheat seedling were administered at 0.6 mg/kg and 142 mg/kg for 30 days respectively. While the comparative evaluation wheat seedling and statin of ultrox in blood serum on the automated biochemical analyzer (RX Daytona/Randox, Great Britain) the content of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol(HDL), low-density lipoprotein, very low-density lipoprotein (LDL) were determined and the atherogenic coefficient (AC) was calculated. Results: There was a significant decrease in the saturated blood content and an increase in polyunsaturated fatty acids such as linoleic and linolenic acids. The use of both the ultrox and wheat seedling had a distinct positive effect on the spectrum of high- and low-density lipoproteins, more significant lipid-lowering effect. Conclusion: The present study indicates that wheat seedling can be prescribed to reduce the dose of statin in their blood.